DEVELOPMENT OF A DECENTRALIZED SERVICE REGISTRY SYSTEM USING IOTA TANGLE - Novendra Wahyunadi, Eka
The Internet of Things is an example where the exchange of information between machines occurs. IoT technology can enter many industrial sectors, therefore IoT can develop rapidly. Therefore, the use of a service registry that acts as a place to search for IoT services will increase. Most of the existing service registry are still running centrally, therefore to meet the need for a decentralized service registry, a service registry system was developed using IOTA Tangle. The result of the implementation of this solution is a smart contract that runs on the IOTA network, and a gateway node as an interface to the IOTA network. The service registry system that has been developed is able to meet functional requirements, namely service registration, service renewal, service deletion, service search, service description retrieval, and retrieval of services that has been registered. In terms of performance for registration, renewal and deletion of services, the system is quite good, because the response time obtained is quite constant at less than 1 second even though the number of services registered in the system continues to grow. However, for service search, service description retrieval, and retrieval of services that have been registered, the system performance is not very good because response time continues to increase linearly along with the increase in the number of service entries in the system. Furthermore, it was also found that the performance of service search is not too influenced by the number of attributes possessed by a service or the attributes used to perform searches